FTY720-derivatives do not induce FTY720-like lymphopenia - Ismael Segura-Ulate; Troy K. Belcher; Guadalupe Vidal-Martinez; Javier Vargas-Medrano; Ruth G. Perez (Elsevier, 2017)
FTY720 is an immunosuppressive multiple sclerosis (MS) drug that stimulates the expression of neuroprotective brain-derived-neurotrophic-factor (BDNF). In vivo preclinical data suggest that FTY720 could be beneficial for treating Parkinson's patients, though its immunosuppressive effects might limit its efficacy. Two novel FTY720-derivatives, FTY720-C2 and FTY720-Mitoxy, also stimulate BDNF expression and enter brain like FTY720 but are not phosphorylated, suggesting they will not produce FTY720-like immunosuppression. Using FTY720 as a positive control, we measured low and high dose FTY720-derivatives, which did not stimulate FTY720-like lymphopenia or immunosuppressive signaling. These findings support the further preclinical assessment of the derivatives as potential novel Parkinson's therapies.